The Influence of Leadership, Work Environment, and Motivation on Change Management In Improving Employee Performance (a Study at The Kuala Tanjung Class III Port Authority and Harbor Master's Office) - Gresnani Panjaitan; Hendrian Hendrian; Sri Gustina Pane (Eduvest - Journal of Universal Studies, 2025)
This study investigates the influence of leadership, work environment, and motivation on employee performance, with change management as a mediating variable, at the Kuala Tanjung Class III Port Authority and Harbor Master's Office. Employing a quantitative explanatory approach with Structural Equation Modeling (SEM) through SmartPLS, data were collected from 79 active employees using purposive sampling. The findings reveal that leadership, work environment, and motivation positively and significantly influence both change management and employee performance. Critically, change management serves as a significant mediator, strengthening the relationship between these organizational factors and performance outcomes. The path coefficients indicate that motivation exerts the strongest influence on change management (β=0.470), while change management demonstrates substantial direct effects on employee performance (β=0.408). These results underscore the strategic importance of implementing participative and transformational leadership, fostering supportive work environments, and sustaining employee motivation through systematic reward and development programs. The study contributes theoretically by validating change management as a critical mediating mechanism in public sector organizations, and practically by providing evidence-based guidance for enhancing organizational adaptability and employee performance in port authorities facing contemporary operational challenges.